Rooting out hunger in Malawi transitioning into a National Roots and Tuber development program - Mueller, E. (International Potato Center, 2015)
The Rooting Out Hunger project is implemented in in Chikwawa, Phalombe, and Zomba districts and is extending into neighboring Blantyre, Chiradzulu, Mwanza, and Nsanje districts; all located in Southern Malawi. The first phase focused on promoting the adoption and appropriate use of orange-fleshed sweetpotato (OFSP) as a food-based approach in reducing malnutrition and poverty levels in Malawi. This document briefly highlights the lessons learnt in the first phase and the plans for the second that will run from 2016 to 2020, in which production of OFSP, cassava and potato will be scaled up and expanded.